The QR Method: A Step-by-Step Guide to Writing a Narrative Review (Islas, 2025)
Introduction: Narrative reviews have been widely used in research, but they lack standardized methods, especially in the social sciences and humanities. Hence, the objective of establishing the QR method (Questions & Reproducibility) is to improve the rigor and transparency of these reviews.Methods: The study adopted a qualitative approach and longitudinally used the systematization of experiences in five editions of a scientific writing course. A total of 126 social science and humanities students participated, forming a training group. In addition, interviews with experts and bibliometric analysis were conducted.Results: The findings show that the application of the QR method significantly improves the quality of narrative reviews, highlighting a higher index of (1) structure, (2) argumentative coherence, (3) methodological rigor and traceability, and (4) effective completion. Interviews with experts confirmed the need to provide narrative reviews with clear methodological structures that respect their interpretive flexibility, highlighting the principles of guiding questions and reproducibility as central axes. Bibliometric analysis revealed sustained growth in this type of review, with a predominance in biomedical areas and scarce representation in the social sciences, as well as a notable absence of specific methodological guidelines, reinforcing the relevance of the proposed method.Conclusion: The QR method has established itself as an effective approach for narrative reviews, improving their clarity, replicability, and standardization, and enabling them to constitute a theoretical-contextual synthesis based on the best available scientific evidence. The study has some limitations, like the small number of experts interviewed and the focus on social sciences and humanities, which limits how much it can be generalized. It's recommended to validate the QR method in other disciplines and real publishing contexts. Future research could follow up on its application in high-impact journals and AI-assisted environments.
Keywords: systematic review; narrative review; scoping review; scientific article; scientific writing